The impact of the UK COVID-19 lockdown on the screening, diagnostics and incidence of breast, colorectal, lung and prostate cancer in the UK: a population-based cohort study - Barclay, NL; Pineda Moncusí, MP; Jödicke, AM; Prieto-Alhambra, D; Raventós, B; Newby, D; Delmestri, A; Man, WY; Chen, X; Català, M (Frontiers Media, 2024)
Introduction: The COVID-19 pandemic had collateral effects on many health systems. Cancer screening and diagnostic tests were postponed, resulting in delays in diagnosis and treatment. This study assessed the impact of the pandemic on screening, diagnostics and incidence of breast, colorectal, lung, and prostate cancer; and whether rates returned to pre-pandemic levels by December, 2021.